Penerapan pembelajaran berdiferensiasi konten melalui model pembelajaran jigsaw untuk meningkatkan keterampilan berpikir kritis siswa - Relly Kristi Yanto Suan; Fakhruddin; Aurelia Astria L. Jewaru; Markus Simeon K. Maubuthy (UNIB Press, 2026)
This study aimed to determine the difference in the improvement of students’ critical thinking skills between content differentiated learning through the jigsaw learning model and the jigsaw learning model without content differentiation, as well as to determine the effectiveness of content differentiated learning on students’ critical thinking skills. This study employed an experimental method with a Pretest-Posttest Control Group Design. The sample consisted of two classes at SMA Negeri 1 Fatuleu Tengah, namely the experimental class and the control class. Data collection techniques included critical thinking tests, observations, and documentation. Data analysis used normality tests, homogeneity tests, initial equivalence tests using Mann–Whitney, and Mann–Whitney U tests. The results showed that the initial abilities of both classes were relatively equivalent with a significance value of 0.319 (>0.05). After treatment, the posttest results obtained a significance value of 0.032 (<0.05), indicating a significant difference between the experimental and control classes. Therefore, content differentiated learning through the jigsaw model proved to be more effective in improving students’ critical thinking skills than the jigsaw model without content differentiation.